2005
DOI: 10.1126/science.1106644
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Methane Emissions from Global Space-Borne Observations

Abstract: Our iterative maximum a posteriori (IMAP) DOAS algorithm (12) is based on optimal estimation (S1,S2) and uses the depth of the absorption structures of the respective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
414
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 422 publications
(448 citation statements)
references
References 24 publications
31
414
1
2
Order By: Relevance
“…The combined datasets provide the longest time series of globally averaged CH 4 abundance. Since the early 2000s, remotely sensed retrievals of CH 4 have provided CH 4 atmospheric columnaveraged mole fractions (Buchwitz et al, 2005a;Frankenberg et al, 2005;Butz et al, 2011;Crevoisier et al, 2009;. Fourier transform infrared (FTIR) measurements at fixed locations also provide methane column observations .…”
Section: Atmospheric Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined datasets provide the longest time series of globally averaged CH 4 abundance. Since the early 2000s, remotely sensed retrievals of CH 4 have provided CH 4 atmospheric columnaveraged mole fractions (Buchwitz et al, 2005a;Frankenberg et al, 2005;Butz et al, 2011;Crevoisier et al, 2009;. Fourier transform infrared (FTIR) measurements at fixed locations also provide methane column observations .…”
Section: Atmospheric Observationsmentioning
confidence: 99%
“…The atmospheric observation density has improved in the tropics with satellite-based column-averaged methane mixing ratios (Buchwitz et al, 2005b;Frankenberg et al, 2005;Butz et al, 2011). However, the optimal usage of satellite data remains limited by systematic errors in satellite retrievals (Bergamaschi et al, 2009;Locatelli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our basic retrieval approach for δD largely follows retrievals from SCIAMACHY (e.g., Frankenberg et al, 2005aFrankenberg et al, , 2008Frankenberg et al, , 2009) using the IMAP-DOAS (Iterative Maximum a Posteriori-Differential Optical Absorption Spectroscopy) algorithm (Frankenberg et al, 2005b) with instrument-specific adaptions and ECMWF meteorological data for pressure, temperature and a priori humidity profiles. CO 2 is the only interfering species, and the disk-integrated solar line-list is adapted from the full-physics CO 2 retrievals used for GOSAT (originally developed for TCCON retrievals).…”
Section: Hdo/h O Retrieval Setup From Gosatmentioning
confidence: 99%
“…The atmospheric CH 4 concentrations have been doubted since preindustrial time (Frankenberg et al, 2005), and most of the CH 4 is produced from fossil fuel combustion, wetlands, rice paddies, waste management and ruminants (Zhuang et al, 2009). Over the past decade, researchers have suggested that CH 4 emissions from reservoirs contribute considerably to anthropogenic CH 4 (Giles, 2006;Zheng et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%